PAI teachers' strategies in developing the religious character of students at SMK Igasar Pindad Bandung - Alamsyah, M Farizal; Sutiawati, Siti; Nulhakim, Ihsan; Nuralisa, Alis; Muhsin, Muhsin (Educenter : Jurnal Ilmiah Pendidikan, 2024)
Research on the strategy of Islamic Religious Education teachers in developing the religious character of students at SMK Igasar Pindad Bandung. Religious character building is the process of forming an atmosphere of religious life. Islamic Religious Education is seen as a strategic means to instill a moral foundation, ethical values, and positive character in students. The purpose of this research is to find out the teacher's strategy in developing the religious character of students at SMK Igasar Pindad. This research uses a qualitative approach with a case study type. The research subjects were selected using purposive sampling technique, selected based on certain criteria to ensure researchers collect as much information as possible from various sources. Data collection techniques used observation, interviews, and documentation. The results of the study found that the strategy of developing the religious character of students is through habituation programs. the success of PAI teachers in developing the religious character of students through habituation and exemplary. Indicators of success in developing the religious character of students at SMK Igasar Pindad Bandung are in accordance with the Ministry of Education and Culture's religious character indicators. According to the Ministry of Education and Culture, the indicators of religious character are as follows: 1) Participating in class learning, namely praying before and after doing work. 2) Obedience to worship, having facilities used for worship and celebrating religious holidays 3) Maintaining environmental cleanliness at school 4) Cooperation between adherents of other religions and beliefs.